Analisis Kelayakan Pendapatan Nelayan Metode CBA, ATF, WTP dalam Peningkatan Kepesertaan BPJS Ketenagakerjaan Indramayu - Rima Kania; Asep Dadan Suhendar (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Fishermen are informal sector workers who face high occupational risks and unstable income derived mainly from fish catches. This study aims to analyze the feasibility fishermen’s income in supporting participation the BPJS Ketenagakerjaan program and to identify the obstacles and solutions in increasing participation based on income feasibility using the Cost Benefit Analysis (CBA), Ability to Pay (ATP), and Willingness to Pay (WTP) approaches. The research was conducted using a quantitative descriptive method with primary data obtained through questionnaires and interviews with fishermen. The results the CBA indicate that the benefits received from BPJS Ketenagakerjaan participation exceed the contribution costs paid by fishermen, demonstrating positive economic feasibility. The ATP analysis shows that, on average, fishermen have the financial capacity to pay the required contributions despite fluctuating and seasonal income patterns. Meanwhile, the WTP analysis reveals that fishermen are generally willing pay contributions after understanding the benefits provided, although the willingness level is not yet optimal and remains lower than their actual ability pay.Overall, the integration of CBA, ATP, and WTP results confirms that fishermen’s income from fish catches is financially feasible to support BPJS Ketenagakerjaan participation. The main obstacles to increasing participation are not related to income feasibility but rather non-financial factors, such as limited social security literacy, insufficient information dissemination, and contribution payment mechanisms that are not fully adapted fishermen’s income characteristics. Therefore, strategic solutions implemented by BPJS Ketenagakerjaan—such as strengthening socialization, simplifying procedures, and developing more flexible contribution schemes—are essential to enhancing participation sustainability among fishermen.